Effectiveness and experiences of families participating in peer led parenting support programs delivered as home visiting programs and the meaning they attribute to these support programs: a systematic review protocol - Munns, Ailsa; Hegney, Desley; Walker, R. (Joanna Briggs Institute, 2014)
Review question/objective: What is the effectiveness and experience of families participating in peer led parenting support programs delivered as home visiting programs? The objective of this review is to identify the effectiveness and experience of families participating in peer led parenting support programs delivered as home visiting programs. The quantitative objective is to identify the effectiveness of peer led home visiting parent support for families. More specifically, the objectives are to identify: The types of peer led home visiting programs that are, or have been undertaken. The effectiveness of peer led home visiting parent support programs on families. The qualitative objectives are to identify the experiences and meanings of peer led parenting support programs for families. More specifically, the objectives are to identify the evidence on: The meaning that families place on peer led home visiting parent support programs. The experiences of families with regard to peer led home visiting parent support programs. The successful components of peer led home visiting parent support programs. The differences between peer led home visiting programs offered to Indigenous and non-Indigenous families.Inclusion criteria: Types of participants: The quantitative and qualitative components of this review will consider studies that include: 1. Families/parents (including Indigenous and non-Indigenous) with one or more children aged 0-4 years of age. Parents may be married, single or in defacto and/or same sex relationships. 2. Parent/Peer support workers.Exclusion Criteria: All exclusion criteria are addressed in the relevant sections of the protocol. Types of intervention(s)/phenomena of interest: Peer led parenting support programs delivered as home visiting programs include the use of volunteer or paraprofessional parents who have shared similar parenting experiences in the local community.The quantitative component of the review will consider studies that evaluate the effectiveness of peer led home visiting parent support programs for families/parents with children 0-4 years of age. Interventions delivered as non-home visiting support or delivered with non-peer support will not be included. The qualitative component of this review will consider studies that investigate the meaning and experiences of peer led parenting support programs for families with children 0-4 years of age.